Teknik Persuasi dalam Komunikasi Agama: Studi Kasus Program “Kurban sampai Pelosok” UNS Surakarta - Sihabuddin; Riyanto, Buddy (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2025)
This study examines the persuasive communication strategies employed by the organizers of the